2022
DOI: 10.3390/curroncol29090516
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Salivary Amylase and Xerostomia in Intensity-Modulated Radiation Therapy for Head and Neck Cancer: A Prospective Pilot Study

Abstract: Purpose. A single-institution prospective pilot study was conducted to the assess correlation between salivary amylase and xerostomia in patients with head and neck squamous cell carcinoma (HNSCC) treated with intensity-modulated radiotherapy (IMRT). Methods and materials. Serum saliva amylase, clinician-reported xerostomia (using Common Terminology Criteria for Adverse Events), and patient-reported xerostomia (using 8-item self-reported xerostomia-specific questionnaire) were prospectively collected at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The previous literature has shown that serum amylase may be capable of reflecting acute or chronic salivary dysfunction in head and neck cancer patients undergoing radiotherapy [29,30]. While serum amylase comprises salivary and pancreatic amylase with near-equal proportions [31], measurements of the concentration of amylase directly from saliva seems to be able to represent the salivary gland function without the interference of pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature has shown that serum amylase may be capable of reflecting acute or chronic salivary dysfunction in head and neck cancer patients undergoing radiotherapy [29,30]. While serum amylase comprises salivary and pancreatic amylase with near-equal proportions [31], measurements of the concentration of amylase directly from saliva seems to be able to represent the salivary gland function without the interference of pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…While some natural hydrocolloids contain high degrees of starch, which is composed of low-molecular-weight sugars, such as glucose, maltose, or maltotriose, and is hydrolyzed by α-amylase in saliva, this effect is less pronounced in patients suffering from xerostomia. Studies report not only that the lack of saliva reduces food moistening and bolus formulation but also that the damage of serous salivary cells further results in significantly less α-amylase production [31]. Consequently, polysaccharides from plant extracts could be potential candidates for saliva substitution, without being subject to hydrolyses.…”
Section: Introductionmentioning
confidence: 99%
“…Маркерами ксеростомії (сухість в ротовій порожнині) можуть бути сироватковий альбумін та амілаза [45,46]…”
unclassified